2015
DOI: 10.1016/j.cct.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

VITAL-Bone Health: Rationale and design of two ancillary studies evaluating the effects of vitamin D and/or omega-3 fatty acid supplements on incident fractures and bone health outcomes in the VITamin D and OmegA-3 TriaL (VITAL)

Abstract: Rationale Although vitamin D is widely used to promote skeletal health, definitive data on benefits and risks of supplemental vitamin D alone on bone are lacking. Results from large, randomized controlled trials in the general population are sparse. Data on the effects of supplemental omega-3 fatty acids (FAs) on bone are also limited. Design The VITamin D and OmegA-3 TriaL (VITAL) is a double-blind, placebo-controlled trial assessing the role of vitamin D3 (2000 IU/d) and omega-3 FA (1 g/d) supplements in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 73 publications
0
25
0
4
Order By: Relevance
“…An ancillary VITAL study will comprehensively test effects of supplemental vitamin D and/or omega-3 on skeletal health by using DXA scans to assess changes in bone and body composition with vitamin D and omega-3 fatty acid supplementation. 80 Results from VITAL will help clarify the relationship between supplemental vitamin D and adiposity outcomes, and inform clinical care and public health guidelines on the use of supplemental vitamin D in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…An ancillary VITAL study will comprehensively test effects of supplemental vitamin D and/or omega-3 on skeletal health by using DXA scans to assess changes in bone and body composition with vitamin D and omega-3 fatty acid supplementation. 80 Results from VITAL will help clarify the relationship between supplemental vitamin D and adiposity outcomes, and inform clinical care and public health guidelines on the use of supplemental vitamin D in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 20 ancillary studies have received independent funding to evaluate the effect of vitamin D and omega-3 fatty acid supplementation on other outcomes, including diabetes, hypertension, cognitive decline, autoimmune diseases (e.g., thyroid disease, rheumatoid arthritis, and lupus), physical disability and falls, bone health and fractures (33), anemia, macular degeneration, dry eye syndrome, infections, asthma, depression, diabetes-related kidney disease, kidney function in people with hypertension, chronic knee pain symptoms, and atrial fibrillation.…”
Section: Methodsmentioning
confidence: 99%
“…Anu Gupta et al [180] in a randomized controlled open-label trial, found that patients with acute ischaemic stroke that received vitamin D and calcium supplementation, along with usual care, compared to those receiving usual care alone, presented a greater probability of survival, achieving a better outcome at 6 months compared to controls. Concerning Stroke, the VITamin D and OmegA-3 triaL (VITAL) studied the effect of supplementation on total cancer and major cardiovascular events (a composite of myocardial stroke, and death due to cardiovascular events), thus reporting significant effects only on reduction of bone fractures [181][182]. Similarly, the benefit of vitamin D supplementation for stroke related depressive symptoms is still debated [183].…”
Section: Vitamin D Deficiency and Ischemic Strokementioning
confidence: 99%